Impact of PLCG2 expression on Microglial Biology and Disease Pathogenesis in Alzheimer's Disease. (31st December 2021) - Tsai, Andy Po‐Yi; Lin, Peter Bor‐Chian; Dong, Chuanpeng; Moutinho, Miguel; Liu, Yunlong; Bissel, Stephanie J; Oblak, Adrian L; Nho, Kwangsik; Lamb, Bruce T.; Landreth, Gary E
Abstract: Background: Alzheimer's disease (AD) and other neurodegenerative diseases are typified by a robust microglial‐mediated immune response. Genetic studies have demonstrated that variants in microglial genes are linked to risk for AD. Phospholipase C gamma 2 (PLCG2), whose variants confer altered risk for AD, is a critical signaling element for various immune receptors and is a key regulatory hub gene for immune signaling. To date, it is known that PLCG2 might be important in AD due to the pervious findings that a hypermorphic variant in PLCG2, rs72824905, is protective against AD risk. However, the role of PLCG2 has not yet been comprehensively explored. We believe that genetic mouse models are needed to further clarify the role of PLCG2 in plaque‐associated microglia and to determine whether decreased PLCG2 expression in plaque‐associated microglia favors disease exacerbation or attenuation. Method: To investigate the impact of reduced PLCG2 gene expression on microglia biology and disease pathology, we have generated PLCG2 inactivation mice, all crossed onto the 5XFAD amyloidogenic murine model of AD. Result: We provide data demonstrating that in individuals with AD, there is increased expression of PLCG2 in the brain, a finding that is recapitulated in 5XFAD mice. We show that reduced PLCG2 gene expression program microglial phenotypes in 5XFAD mice, affect plaque pathology, and drive distinct transcriptional phenotypes of microglia in the presence of amyloid pathology. Analysis of plaque pathology revealed that 5XFAD PLCG2 inactivation mice have elevated plaque burden. Compared to 5XFAD mice, behavioral analysis of 5XFAD with PLCG2 inactivation mice demonstrated an impaired performance in the Y maze assay, reflecting impaired cognitive decline. Our data suggest that the inactivation of PLCG2 had accelerated and exacerbated disease‐related pathology. Conclusion: Together, our findings provide evidence that PLCG2 plays an important role in AD pathophysiology, indicating PLCG2 as a potential new therapeutic target for AD.